Histological Studies of Snails at Different Periods of Their Life Activity - I. S. Danilova; T. I. Fotina; T. M. Danilova (Ukrainian Journal of Veterinary and Agricultural Sciences, 2022)
Large species of terrestrial mollusks are used for human consumption and are bred for this purpose. They have become a part of national cuisine in many countries. Histology is used in many fields of humane and veterinary medicine. Its main essence is that this method can diagnose the presence of formations and inclusions. It is used to determine this process's structure and stage of development. Samples of different tissues can be used as material for histological examination. The specialist analyzes and describes the histological preparations obtained after processing the material. Thus, we proposed a histological method of studying snails. This method can provide the data of snails’ state as a whole. Snails of the species Helix aspersa maxima, Helix aspersa muller, and Helix pomatia were the material for the study. Ten snails of each species were selected for the experiment at different periods: immediately after hibernation, five days after wakening, 14 days after wakening, and at the time of their active life – in July. First, we conducted histological studies of snails during their active life, i.e., in the summer months. Therefore, for this purpose, snails for the experiment were taken in July. It was determined that if the snail eats and has an everyday life, its digestive gland generally consists of digestive tubules separated by intertubular connective tissue containing hemolymphatic sinuses and hemocytes. Thus, in our research, we studied the structure of the digestive gland. A circular muscle layer surrounds each tubule. There are three different cell types in the epithelium lining the tubules of the digestive glands, which differentiate into digestive cells, calcium cells, and excretory cells. Digestive cells are the most numerous cellular component of the tubular epithelium of the digestive gland. Basally located nuclei of digestive cells have a round or oval shape. During the rest period, the digestive gland of snails is characterized by a complete loss of digestive function and the transformation of digestive cells into excretory ones. Metabolic products are not excreted into the environment. When they accumulate, they fill all cavities in the body of snails, namely the lumens of glandular tubules, excretory ducts, stomach, and intestines. Food intake in snails increases the level of metabolism. It stimulates the differentiation of digestive cells, the functional activity of excretory cells, and the volume of excretory products. It leads to the complete liberation of the digestive tract from accumulated excretion products during the rest period. The structure of the digestive gland is completely restored.